Hemophagocytic lymphohistiocytosis associated with oxcarbazepine - Kırık, Serkan; Güneş, Hatice; Yurttutan, Sadık; Sarışık, Nafiz; Acıpayam, Can; Kırık, Yasemin (The Turkish Journal of Pediatrics, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is a rare life-threatening multisystem disorder. Reports of the disorder as a side effect of drugs are extremely rare. We report the case of a 3-year-old boy with a history of epileptic seizures in which oxcarbazepine was added to treatment for the last 35 days and dose had been increased. For 10 days he had a fever, hepatosplenomegaly, rash, edema and other systemic symptoms. He was diagnosed with HLH after bone marrow examination. Oxcarbazepine treatment was terminated after the intravenous immunoglobulin treatment. The next day, clinical and laboratory results had improved. This is the first HLH report of an association with oxcarbazepine. Bone marrow aspiration may be indicated to confirm the diagnosis when facing a patient with systemic symptoms after newly added antiepileptic drug treatment.